Sleep in Isolated, Confined, and Extreme (ICE): A Review on the Different Factors Affecting Human Sleep in ICE - Zivi, Pierpaolo; De Gennaro, Luigi; Ferlazzo, Fabio (Frontiers in Neuroscience, 2020)
The recently renewed focus on the human exploration of outer space has boosted the interest toward a variety of questions regarding health of astronauts and cosmonauts. Among the others, sleep has traditionally been considered a central issue. To extend the research chances, human sleep alterations have been investigated in several analogue environments, called ICEs (Isolated, Confined, and Extreme). ICEs share different features with the spaceflight itself and have been implemented in natural facilities and artificial simulations. The current paper presents a systematic review of research findings on sleep disturbances in ICEs. We looked for evidence from studies run in polar settings (mostly Antarctica) during space missions, Head-Down Bed-Rest protocols, simulations, and in a few ICE-resembling settings such as caves and submarines. Even though research has shown that sleep can be widely affected in ICEs, mostly evidencing general and non-specific changes in REM and SWS sleep, results show a very blurred picture, often with contradictory findings. The variable coexistence of the many factors characterizing the ICE environments (such as isolation and confinement, microgravity, circadian disentrainment, hypoxia, noise levels, and radiations) does not provide a clear indication of what role is played by each factor per se or in association one with each other in determining the pattern observed, and how. Most importantly, a number of methodological limitations contribute immensely to the unclear pattern of results reported in the literature. Among them, small sample sizes, small effect sizes, and large variability among experimental conditions, protocols, and measurements make it difficult to draw hints about whether sleep alterations in ICEs do exist due to the specific environmental characteristics, and which of them plays a major role. More systematic and cross-settings research is needed to address the mechanisms underlying the sleep alterations in ICE environments and possibly develop appropriate countermeasures to be used during long-term space missions.